Analysis of the academic permanence of students of the science course of the nature of the Uruguayana campus (Research, Society and Development, 2020)
The present study is an investigation about the permanence of students, participants by affirmative actions in the course of Nature Sciences of the Campus Uruguaiana of Unipampa. The purpose of this study was to contribute to a better understanding of the academic course of students who entered the system of quotas for income below a minimum wage and a half. The data were collected from the academic records platforms of the institution and analyzed quantitatively using basic elements of mathematics by percentage. The analysis of the results showed a high number of students evading between the ages of two and thirteen and two thousand and seventeen, reaching more than forty-nine percent, of the quota holders by income. The data demonstrate that an effective policy for access to higher education is not enough, and that a public policy aimed at permanence is also necessary, and should be constantly discussed and new strategies established in order to minimize the phenomenon of avoidance.